PEMBERDAYAAN EKONOMI MASYARAKAT MUSLIM MELALUI KEGIATAN JAM’IYAH ARISAN DI DESA JATIBOGOR KECAMATAN SURADADI KABUPATEN TEGAL - Akhris Fuadatis Sholikha (el-Jizya : Jurnal Ekonomi Islam, 2019)
This study aims to examine the factors that influence the level of economic empowerment of Muslim communities through the activities of jam'iyah arisan. Where are the factors that influence the level of community empowerment, namely physical capital, human capital, social capital, empowerment actor groups (KPP) and empowerment. Samples were taken from female jam'iyah members in the village of Jatibogor. This research is a quantitative study using PLS (Partial Least Square) data analysis. The results showed that the empowerment actor group variables, physical capital, human capital, social capital, and empowerment had no effect on empowerment. KPP variables, physical capital, and human capital had no effect on social capital. KPP, physical capital, human capital, and social capital had no effect on empowerment.